Insights into IL-23 biology: From structure to function. Issue 5 (October 2015) - Floss, Doreen M.; Schröder, Jutta; Franke, Manuel; Scheller, Jürgen
Highlights Interleukin (IL-)23 is a central cytokine controlling TH17 development. Overshooting IL-23 signaling contribute to autoimmune diseases. IL-23 is a member of the IL-12-type cytokine family and consists of IL-23p19 and p40. IL-23 triggers heterodimerization of IL-12Rβ1 and the IL-23R.